Factors that influence actual playing time: evidence on chinese football association super league - Zhang, G.; Wang, J.; Li, S.; Cao, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The actual playing time of football is a crucial index for assessing the excitement and caliber of a league. With advancements in data tracking technology in football matches, the statistical analysis of net duration has progressively become more efficient and convenient. A study has conducted to explore factors influencing actual playing time of Chinese Football Association Super League (CSL). METHODS: 40 factors were classified into quantifiable(n=9) and non-quantifiable (primary = players, team, character of a game, referee, and others, secondary =26) indicators. Entropy method was used to ascertain the weights of quantifiable indicator. The magnitude of dispersion is positively correlated with the impact of the indicator on the comprehensive evaluation. The data encompasses from 240 matches involving 16 teams in the CSL during season 2018. For non-quantifiable indicators, 40 experts specializing in football were invited to evaluate these indicators through a structured questionnaire. Following the principal component analysis method was to derive the weights for each indicator. The weights of primary indicators are composed by aggregating the secondary indicators. RESULTS: For quantifiable indicators, the highest weights of indicator were the opponents free kicks in their own half (0.1760), followed by the restart of play after scoring a goal (0.1738), and throw-ins (0.1302). For non-quantifiable indicators, the weight of player was 0.1920, which influenced by the top three secondary indicators being subjective procrastination intent (0.0447), aggressiveness (0.0432), and physical fitness (0.0405). The weight of team was 0.1805, which influenced by the top three secondary indicators being home and away performance (0.0409), tactical execution level (0.0367), and the degree of coordination (0.0356). The weight of character of a game was 0.0785 comprising by match attributes (0.0407) and the disparity in strength between the two sides (0.0378). The weight of referee was 0.1917, which influenced by the top three secondary indicators being officiating proficiency (0.0405), judgment scale (0.0388), and team coordination (0.0384). The weight of other factors was 0.3517, which influenced by the top three secondary indicators being on-field violent incidents (0.0442), on-field special events (0.0418), and medical support measures (0.0414). CONCLUSION: The actual playing time in CSL games was affected by multiple factors. These results provide a reference for practitioners to design effective training and formulate game strategies for elite soccer leagues. Chinese Football Association needs to set out a series of specific measures based on the weights of different factors, and encourage all relevant organizations to take measures to enhance the continuity, quality, and watchability of a match, elevating the standard of Chinese football to align with international norms.